PENGARUH SUBSTITUSI TEPUNG BATANG NANAS (ANANAS COMOSUS) DAN RED KIDNEY BEAN (PHASEOLUS VULGARIS) TERHADAP DAYA TERIMA, KADAR PATI RESISTEN & PROTEIN PADA MI INSTAN - Yama Dharma Putera; Annis Catur Adi (Universitas Airlangga, 2021)
Instant noodle is one of the most popular food in Indonesia because of the fast preparation and easily accepted by people.. However, the nutritional content and overeating instant noodle, become one of the causes metabolic syndrome which is currently increasing globally. This study was aimed to determine the eff ect of pineapple stem starch fl our and red kidney bean (jogo bean) fl our substitution on wheat fl our towards acceptability, levels of resistant starch and protein in instant noodle. The research was done by using a true experimental with a randomized design consisted of the control formula (F0), F1 substitution formula (5% pineapple stem fl our and 20% jogo bean fl our) and F2 (7% pineapple stem fl our and 28% jogo bean fl our). A total of 27 person were involved as semi-trained panelists, acceptance level was tested by Kruskall-Wallis and continued by the Mann-Whitney if the diff erence appeared signifi cant (α≤ 0.05). Resistant starch and protein content will be compared between theoretical calculations from Indonesia Food database and some research with laboratory tests. Acceptance test results state that the most favored substitution formula by panelists is F2 (28% jogo bean fl our and 7% pineapple stem fl our). The highest protein content and resistant starch was found in F2 (14.4 g and 11.3 g). Signifi cant diff erences were seen between F0 with F1 and F2 in the characteristics of color acceptability (p = 0.001) and texture (p = 0.008). Consumption of instant noodles substitution formula F2 with adding a half egg can meet the recommended consumption of one meal of resistant starch and protein which has benefi ts in preventing the metabolic syndrome.